Stereotactic Ablative Body Radiotherapy (SABR) in The Management Spinal Metastases: A Brief Overview* - KODRAT, HENRY; GONDHOWIARDJO, SOEHARTATI (Indonesian Journal of Cancer, 2017)
It is well known that radiotherapy provides successful pain relief in bone metastases. Advancements in imaging and radiotherapy delivery technology have enabled safe delivery of higher dose radiotherapy, which will produce more durable tumor control. Over the last decades stereotactic radiosurgery (SRS), which delivers high dose radiation, has been successfully used for the treatment of intracranial lesions. The good results obtained in SRS have led to development of extra cranial stereotactic radiosurgery known as stereotactic ablative body radiotherapy (SABR). This review paper enlightens indication, target definition, efficacy and toxicity in spinal SABR.ABSTRAK Radioterapi telah terbukti sebagai modalitas yang dapat menghilangkan nyeri pada metastases tulang. Kemajuan dalam teknologi pencitraan dan pemberian radioterapi telah memungkinkan pemberian radioterapi dosis tinggi dengan aman, di mana hal ini dapat meningkatkan kontrol lokal. Selama dekade terakhir ini, stereotactic radiosurgery (SRS) yang memberikan radiasi dosis tinggi dinyatakan bermanfaat untuk tatalaksana berbagai kelainan intrakranial. Hasil cukup memuaskan yang diperoleh SRS mendorong untuk dikembangkan stereotactic radiosurgery ekstrakranial yang kemudian dikenal sebagai stereotactic ablative body radiotherapy (SABR). Tinjauan pustaka ini menjelaskan indikasi, target radiasi, efektivitas, dan efek samping pada prosedur SABR spinal.